Prediction of ultimate load bearing capacity of driven piles [electronic resource] - 214467 Wong, Charng Chen (Skudai : Universiti Teknologi Malaysia, 2006)
Thesis (Sarjana Kejuruteraan (Awam - Geoteknik)) - Universiti Teknologi Malaysia, 2006